Cultural and legal perspectives of marital rape issues in Nigeria (2020)
Marital rape, also known as, Spousal Rape is a form of domestic violence, public health challenge, and human right issue which occurs whenever a husband has sex with his wife without seeking her consent. It is similar to the offence of rape with the major distinction of the existence of marriage between the parties involved. Although the offence of rape is criminalised in Nigeria, marital rape is not. The major reason for this is not far-fetched: the patriarchy cultural system practiced in Nigeria elevates a husband to the position of dominance while it robs a wife of her privacy, liberty, sexuality and renders her to become her husband’s property, thus, he can ‘lawfully’ rape her in marriage and not act illegally. Due to this, a lot of women '-suffer silently in the hands of their husbands, and some even die. Therefore, in a bid to resolve the problem of marital rape in Nigeria, this article defined some related concepts to marital rape; determined the prevalence of the latter globally; analysed the extant laws on rape and '-non-recognition of marital rape; study the patriarchy cultural system practiced in Nigeria; examined contending issues in the criminalisation/prosecution of marital rape in Nigeria; and concluded with recommendations.